Nemorilla floralis - DRABER-MOŃKO, Agnieszka (Zenodo, 2015)
Nemorilla floralis (Fallén, 1810) * Tachina floralis Fallén, 1810: 287. Type locality: Sweden. Material examined: Hamgjǒng-pukto Prov., Kjǒngsǒng distr., Džuyr ad Čhǒngdžin, 24. 08. 1959, 1 male, leg. B. Pisarski and J. Prószyński. Distribution: Palaearctic: Europe northwards to Sweden (Herting & Dely-Draskovits 1993), Russia (S. Far East: Primorsk Territory, Sakhalin, S. Kuril Islands: Iturup, Kunashir) (Richter 2004), Japan (Hokkaido, Honshu, Shikoku, Kyushu, Tsushima Island) (Shima 2014). First record from Korea. : Published as part of DRABER-MOŃKO, Agnieszka, 2015, State of knowledge of the tachinid fauna of Eastern Asia, with new data from North Korea. Part V. Exoristinae, pp. 79-98 in Fragmenta Faunistica 58 (2) on page 95, DOI: 10.3161/00159301FF2015.58.2.079, http://zenodo.org/record/6251824 : {"references": ["Richter V. A. 2004. Fam. Tachinidae - tachinids. In: Sidorenko V. S. (ed.), Key to the insects of Russian Far East. Vol. VI. Diptera and Siphonaptera. Part 3 pp. 148 - 398. Vladivostk, Dal'nauka. 657 pp. [In Russian].", "SHIMA H. 2014. Family Tachinidae. In: NAKAMURA, T., SAIGUSA, T. & SUWA, M. (eds.), Catalogue of the insects of Japan. Volume 8. Diptera. Part 2. Brachycera Schizophora, pp: 832 - 882. Entomological Society of Japan, Fukuoka, XIV + 562 pp."]}